Reforming Education Finance in Transition Countries : Six Case Studies in Per Capita Financing Systems - Alonso, Juan Diego; Sánchez, Alonso (World Bank, 2012)
This book reviews the experience with one specific though widely introduced approach to funding general education, namely per capita financing (PCF), in six countries in the Europe and Central Asia (ECA) region in an effort to learn which outcomes were achieved and how. Per capita financing is a type of formula funding of schools-funding characterized by a set of agreed objective criteria for allocating resources to schools, that provides schools fixed amounts of financing based on the numbers of students enrolled. Five of the six case study countries, Armenia, Estonia, Lithuania, Poland and the Russian Federation, were chosen primarily since they represent ECA countries with relatively long experience in implementing PCF schemes. The hope is that, as a result, the likelihood of observing the outcomes of per capita financing is higher. Since per capita financing replaced a school budget allocation process (input-based or normative budgeting) that was non-transparent and conducive to inefficient use and inequitable allocation of resources, the main expected outcomes of the per student finance reform were improved efficiency, equity, and transparency and accountability of public education expenditures.